Reproductive potential of Algerian she-camel for meat production - A Case of the Region of Souf - Brahimi, Zakaria; Said, Bezziou; Abdelhakim, Senoussi (Journal of Research in Biology, 2018)
The current research was done to study the reproductive performances of Algerian she-camel for meat production. The study was conducted from March 2006 to May 2016 in Souf region; southeast of Algeria where a total of 71 camel herders were randomly selected for data collection using a questionnaire tool. The study revealed that all camel herders bred camels only for meat production by keeping high breeding rates of females in herds. The survey showed that she-camel Sexual activity Took place in the rainy season extending from October to the beginning of May and intensified between December to January. The mean age at first mating, first calving and gestation length were 45.8 ±0.77, 58±0.76 and 12.1±0.03 months respectively. Calving interval and lactation length were 22.1±0.51 and 13.6±0.56 months respectively. The mean age at culling was 22.7±0.47 years. The average number of births during a reproductive lifespan was 7.33±0.21 calves. The mean birth weight was 20.9±0.49kg. Due to their low reproductive performances, camels are not good suppliers of meat. Reducing age at first parturition and calving interval seems to be a good solution that has to be recommended for better meat productivity.